Investigating and Analyzing the Current Situation of College Students Participating in Local Social Basic Medical Insurance: Based on Empirical Survey from Guangdong Medical University Dongguan Campus - Zhang, Xiao min (Pacific International Journal, 2024)
The health of college students is directly related to the quality and quantity of national talents. Therefore, it is particularly important to guarantee the medical rights and interests of college students, ensuring that they can receive timely and effective treatment when they encounter diseases. However, the current situation of college students participating in local social basic medical insurance is not optimistic. Based on this, this article takes Dongguan Campus of Guangdong Medical University as an example and explores the participation status and influencing factors of college students in social basic medical insurance through questionnaire survey. It also aims to propose targeted suggestions to increase the participation rate of college students in insurance, strengthen their understanding of the importance of medical insurance, and enable them to better enjoy the protection brought by medical insurance, paving the way for their health and future. At the same time, it aims to contribute to the construction of a social medical security environment.